Modernization of Al Washliyah Educational Institutions - Napitupulu, Dedi Sahputra (Universitas Ahmad Dahlan, 2025)
The potential of an educational institution to effectively respond to quickly evolving circumstances significantly influences its long-term viability. Consequently, the ability for educational institutions to adopt modern practices is critical. Al Washliyah, founded in 1930 in Medan, is one of the most sizable Islamic organizations and is credited with establishing numerous educational institutions. Consequently, the objective of this study is to investigate the effect and contribution of Al Washliyah, with a particular focus on the realm of education. Additionally, it seeks to identify the typology of modernization implemented by Al Washliyah educational institutions and to scrutinize the various facets of modernization undertaken by said institutions. For the purpose of accomplishing this objective, a historical lit review was conducted. The findings of this study indicate that the Al Washliyah educational institution has implemented a revitalization strategy, which entails preserving venerable old traditions while incorporating better-regarded innovations into the realm of educational advancement. The modernization of the Al Washliyah educational institution is evident in its human resources (HR), courses of study, institutions, and objectives.